2001
DOI: 10.1002/jid.728
|View full text |Cite
|
Sign up to set email alerts
|

The supply response of basmati rice growers in Punjab, Pakistan: price and non‐price determinants

Abstract: Pakistan's stated policy is to increase basmati rice production through price support measures and liberalization of input markets. The present study assesses the scope for price support policy to achieve growth targets and whether additional assistance is needed from non-price policy measures. The econometric analysis is based on a profit function using farm household survey data from the Punjab. Pakistan for 1995-1996. The results reveal that to achieve production targets, very high support prices are requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 6 publications
3
26
0
Order By: Relevance
“…The general form of the translog profit function, dropping the ith subscript for the farm, is defined as [24,25]:…”
Section: The Profit Function Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The general form of the translog profit function, dropping the ith subscript for the farm, is defined as [24,25]:…”
Section: The Profit Function Approachmentioning
confidence: 99%
“…The elasticity of demand for variable input with respect to output price, P y (η jy ) was computed as [25]:…”
Section: Variable Input Demand and Output Supply Elasticitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The monotonicity property of a translog profit function model holds if the estimated output share is positive (Farooq et al 2001) which was found in our case. The symmetry property was Downloaded by [University of Tennessee, Knoxville] at 02:25 26 December 2014 tested by imposing cross-equation restrictions of equality on the corresponding parameters between the profit function and the four factor demand equations.…”
Section: The Empirical Modelmentioning
confidence: 58%
“…A positive response of output supply (rice or wheat) to its price has been common in Asia since the 1970s. For example, supply response of high-yielding varieties (HYVs) of rice in Bangladesh is estimated at 0.36 (Rahman and Shankar 2009), Basmati rice in Punjab, Pakistan, at 0.27 (Farooq et al 2001) and Mexican wheat in Punjab, India, at 0.63 (Sidhu and Baanante 1981 Note: Variables P i = normalized variable input prices, and Z k = fixed inputs; subscripts F = fertilizer price, W = labor wage, M = animal power price, S = seed price, A = land area cultivated, I = irrigation, L = land suitability, and E = other environmental constraints, based on the estimation of the restricted translog profit function and four variable input share equations with across-equation restrictions (symmetry) and linear homogeneity imposed. * Significant at 10% level (p < .10).…”
Section: Resultsmentioning
confidence: 99%